Ringer’s Lactate versus Isotonic Saline: The Nasal Irrigation Solution of Choice in Chronic Rhinosinusitis - Gurung, Urmila; Devkota, Anuj; Pokhrel, Shishir; Pradhan, Bibhu (Journal of Institute of Medicine Nepal, 2024)
IntroductionNasal douching is a simple and highly effective treatment option for chronic rhinosinusitis. This study aimed to compare the efficacy of Ringer’s lactate versus isotonic saline for nasal irrigation in treating chronic rhinosinusitis (CRS) with or without polyposis using the SNOT-22 score.MethodsThis quasi-experimental study was conducted at the Department of ENT and Head & Neck Surgery, Tribhuvan University Teaching Hospital, from September 2020 to November 2021. Seventy-eight patients aged ≥ 16 years with CRS were included in the study. Patients were grouped into either isotonic saline or Ringer’s lactate groups based on the clinician’s preference. Nasal irrigation was prescribed for four weeks. Pre and post-irrigation SNOT-22 scores were analyzed using paired t-test and Student’s t-test.ResultsA significant improvement in the SNOT-22 scores before and after nasal irrigation was observed in both the Ringer’s lactate (26.76±14.07 vs 14.41±7.92, p